The Influence of Stakeholder Involvement in the Adoption of Digital Technologies in the UK Construction Industry - Boroto Hwabamungu; Paul Shepherd (Informatics)
This study explored stakeholder involvement practice in digitalisation of the construction industry in the UK, and the influence thereof in the adoption of digital technologies. A qualitative interpretive method was followed using a case study approach to collect data. Thematic analysis of twenty-four semi-structured interviews and sixty survey responses, which were conducted with different digital technologies adoption actors in the construction industry, allowed the identification of six final themes depicting the influence of stakeholder involvement in the adoption of digital technologies. The findings indicate that stakeholder involvement influence is a function of its embeddedness in an organisation digitalisation approach. Stakeholder involvement embeddedness in the approach, or lack thereof, dictates how the stakeholder landscape is planned and managed, and how communication between and with stakeholder groups occurs. This is the foundation of digitalisation value creation among stakeholders. The approach is prone to digitalisation limitations and intrinsic determinants of adoption, both of which can be positively impacted through better stakeholder involvement practices. Stakeholder involvement practices are therefore catalytic to the subsequent behaviour change for digital technologies adoption and the extent to which digital technologies become adopted. This paper contextualises stakeholder involvement in the adoption of digital technologies in the construction industry, highlighting the catalytic influence of stakeholder involvement embeddedness in the complex digitalisation activity system and its interplay with industry-specific practices and other digital technology adoption determinants.